Digital Al-Qur'an Learning Media in 4th Grade Al-Qur'an Learning Elementary School: Media Pembelajaran Al-Qur’an Digital pada Pembelajaran Al-Qur’an Kelas 4 Sekolah Dasar - Ilmiah, Farichatul; Nisak, Nur Maslikhatun (Universitas Muhammadiyah Sidoarjo, 2023)
In this study, the validity test used triangulation techniques. The subjects of this study were fourth grade students of SD Muhammadiyah 1 Candi with a total of 18 students. The results showed that: (1) Implementation of digital Al-Qur'an learning media through Qur'an learning in grade IV SD Muhammadyah 1 Candi, digital Al-Qur'an media has many versions, but the version used in SD Muhammadiyah 1 The temple uses the Indonesian Al-Qur'an, because it has a word search feature and when we write a word on the search page, the verses related to the word we are looking for will appear. With this media, students' reading of the Qur'an increases & students like digital Al-Qur'an learning media. (2) The advantages and disadvantages of digital Al-Qur'an learning media through Al-Qur'an learning in grade IV SD Muhammadiyah 1 Candi There are obstacles including, when teaching digital Al-Qur'an learning in class IV SD Muhammadiyah 1 Candi there are mostly children with special needs, therefore the learning process is very slow so that teachers find it difficult to teach digital Al-Qur'an learning. The teacher's solution is to teach a little slowly so that the children with special needs can absorb the learning conveyed by the teacher and the learning process can be resolved or run according to the purpose. The advantages of digital Al-Qur'an learning media: Make it easier for teachers for the learning process. Make it easier for teachers to use tools in the learning process.